Copyright © University of Cambridge. All rights reserved.

Nearly $80$ solutions were sent in! These had many examples that had even answers. We did suggest that you went a bit further and here we have some ideas.

First from Owen from the Montessori School of Wooster, Ohio , USA

A square number subtracted by its self (X squared - X) always has to be even. It will always be a even number because an even number times a odd number ($3 x 3 = 3 x 2$ ) is always even

(ex. $4 x 4 - 4 = 4 x 3 = 12, 5 x 5 - 5 = 4 x 5 = 20$)

Amy from Claremont Primary School in the UK had the following thoughts;

$2 x 2 = 4$

$4 - 2 = 2$ (even)

Answer is even with an even number starting point

$3 x 3 = 9$

$9 - 3 = 6$ (even)

Answer is even with an odd number starting point

Therefore answer is always even. Why?

The answer will always be even because an odd number squared makes another odd number. An even number squared makes an even number. And an even number take away another even number makes another even number. But quite strangely an odd number take away another odd number also makes an even number.

From Jasmine, Arran, Rebecca and Thomas at St. Mary's School Shawbury in England , we had a similar thought;

The answer is even. We know this because, when you square an even number you always get an even number, but when you take an even number away from the number that you now have, you still remain an even number, no matter what number you started with.

When you square an odd number, it should result as another odd number, but when you subtract an odd number, from the number you have now, it will result as an even number.

e.g. Even squared = even - even = even.

e.g. Odd squared = odd - odd = even.

We tried this with $1,2, 3$ digit numbers and they all ended even, we also tried different odd and even numbers and found the same result, all the answers were even.

Olly from Bourton Meadow Academy in England , wrote;

It is always even because the multiples of an even number are even

$(2a)(2a+1) = 6a$

If you use an odd number it is simply this formula backwards

$(2a+1)(2a) = 6a$

Finally Victor and Elliott from Kenakena School in New Zealand ;

$X² - X =$ even. If $X$ is odd. $X²$ is odd. so $X² - X = $ even.

If $X$ is even. $X²$ is even. so $X² - X = $even.

Side proof : how even - even = even and odd - odd = even:

If n and e is an arbitrary whole number, then even = $2n$, so even - even $= 2n - 2e = 2(n - e)$. Thereby, even - even = even.

So odd$ = 2n + 1$. So odd - odd = $2n + 1 - (2e + 1) = 2n - 2e + 1 - 1 = 2(n- e)$.

Thereby, odd minus odd = even.

We had a few very late in the month suggestions from Jack, Daniel, Sophiie, Isobel and Ryan at Keidmarch Primary School

Thank you all for your hard work and the emails.